Cryptocoryne (Araceae) a new generic record for the Flora of Nepal - Rai, S.; Ojha, R.; Bhandari, P. (Rheedea, 2024)
Cryptocoryne Fisch. ex Wydler, a member of family Araceae is herein reported as a new generic record for the flora of Nepal. The newly reported Cryptocoryne retrospiralis (Roxb.) Kunth is an amphibious plant, collected from Eastern Nepal characterize by having the spathe of spirally twisted limb, long cylindrical tube without a collar, elongated to variable spots on the wall of spathe and small spadix inside kettle. Description, illustrations and distributional notes are provided for the verification of the new report.